Konsep Revitalisasi Pelabuhan Juwana Kabupaten Pati - Saraswati, Indah; Buchori, Imam (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Juwana ports is a national port, harbors between islands in the river ofsilugangga which is the gateway to the economy in Pati Regency.The concepts of revitalization of the harbor UPP class III Juwana is necessary because during the reign of the Dutch, this port is an international port with traffic of goods, people and voyage is also very crowded; unfortunately the condition does not continue at this time. The port that should have been a modem port are lagging and lacking in economi meaning to the surrounds community and the development of Pati. Therefore, the formulation of the issue in accordance with the background of the research is why and how the process of revitalization. Juwana port will be done as efforts to improve the economy of surrounding community PATI regency.This analysis is using analytical techniques of Importance Performance Analysis (1PA) and the focusing the technique mix method is a method of qualitative analysis and quantitative analysis methods with analize the performance service, government policies and decreased vitality. From the analysis, it is known that a decrease in the vitality of the port of juwana due to geographic factors, physical factors and factors of Juwana port activity, so that it is necessary to do drafting the revitalization of the Juwana port, they are: ,1) Revitalize the shipping Juwana lines so that ships do not lean or mooring in harbor entrance Juwana resulting rapid silting, 2) Revitalize unloading infrastructure and port infrastruktur, 3) The concept of relocation is greater port positioned to deal with the open sea so that ships with gross tonnage could large mooring or dock in ports.